Law Enforcement of Corruption Crime Abuse of Hospital Medical Devices by State Civil Apparatus - Muh Rafly Nurfaizy; H. M. Said Karim; Nur Azisa (Ikatan Ahli Pengadaan Indonesia (IAPI), 2023)
This study aims to determine (1) the Corruption Criminal Law Policy on the Misuse of Hospital Medical Devices by State Civil Apparatuses. (2) The role of the government in the prosecution of corruption crimes involving the misuse of hospital medical devices carried out by state civil apparatus. The preparation of this thesis uses an empirical legal approach, in which the author looks at law in its real sense and examines how the law works in society.With this research, it is concluded that: The role of criminal law in dealing with criminal acts of corruption in the form of abuse of hospital medical devices committed by the state apparatus is contained in Articles 8, 9, 10, 11, 12, 12B, and Article 23 of the Corruption Law (which adopted Articles 421, 422, 429, and Article 430 of the Criminal Code). The criminal act of corruption for civil servants and/or state administrators is a criminal act of corruption that can only be committed by people who are qualified as civil servants or state administrators.The role of law enforcers in the enforcement of corruption crimes in the abuse of hospital medical devices begins with the submission of reports originating from individuals, community organizations and non-governmental organizations, state institutions and government institutions, and information reports from the internal police, which will then be carried out by an investigation process with the assistance of the police and the Attorney General's Office. If the case file submitted by the investigator is deemed complete and the case can be prosecuted by the public prosecutor, then the public prosecutor then makes an indictment.